2014
DOI: 10.1021/ja411563x
|View full text |Cite
|
Sign up to set email alerts
|

Remarkable Scan Rate Dependence for a Highly Constrained Dinuclear Iron(II) Spin Crossover Complex with a Wide Thermal Hysteresis Loop

Abstract: The abrupt [HS-HS] ↔ localized [HS-LS] spin crossovers of a new triazole-based diiron(II) complex result in a record-equaling thermal hysteresis loop width for a dinuclear complex (ΔT = 22 K by SQUID magnetometer in "settle" mode) and show a remarkable scan rate dependence of only the cooling branch, as revealed by detailed magnetic, DSC, and Mössbauer studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
103
2
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 124 publications
(116 citation statements)
references
References 52 publications
(31 reference statements)
8
103
2
1
Order By: Relevance
“…All measurements for the coordination polymers were taken in settle mode, but to show that there is no significant dependence on scan rate, the plots of M T versus T for the sweep measurements of all complexes are presented in Figure S2 in the Supporting Information, as it has been shown that the scan rate can significantly influence the width of the hysteresis. [25] An overview of all the M T values, the fraction of the HS state, and the SCO behaviour is presented in Table 5. The plots of M T versus T in the temperature ranges of interest for the ST of complexes 1c-1f are displayed in Figure 4.…”
Section: Magnetismmentioning
confidence: 99%
“…All measurements for the coordination polymers were taken in settle mode, but to show that there is no significant dependence on scan rate, the plots of M T versus T for the sweep measurements of all complexes are presented in Figure S2 in the Supporting Information, as it has been shown that the scan rate can significantly influence the width of the hysteresis. [25] An overview of all the M T values, the fraction of the HS state, and the SCO behaviour is presented in Table 5. The plots of M T versus T in the temperature ranges of interest for the ST of complexes 1c-1f are displayed in Figure 4.…”
Section: Magnetismmentioning
confidence: 99%
“…Since SCO can be very sensitive to scan rate, [30] we studied its effect in the hysteresis cycle ( Figure 3a). The heating branch does not change significantly with scan rate.…”
mentioning
confidence: 99%
“…arising from the combination of the SCO metal center and other metal centers [2,[19][20][21][22][23][24]. In particular, dinuclear species have received much attention since they are a simple model for revealing intra-and intermolecular interactions for enhancing cooperativity [25][26][27][28][29][30][31][32][33][34]. From a more practical point of view, the importance of studying the reproducible nature and scan rate dependence of the hysteresis loop and high-temperature SCO with sufficient thermal stability has recently been pointed out in order to define the limiting characteristics of SCO materials [33,[35][36][37][38][39].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, dinuclear species have received much attention since they are a simple model for revealing intra-and intermolecular interactions for enhancing cooperativity [25][26][27][28][29][30][31][32][33][34]. From a more practical point of view, the importance of studying the reproducible nature and scan rate dependence of the hysteresis loop and high-temperature SCO with sufficient thermal stability has recently been pointed out in order to define the limiting characteristics of SCO materials [33,[35][36][37][38][39]. Recently, we have focused on SCO molecules with 1-R-1H-1,2,3-triazole-containing Schiff-base (1-R-1H-1,2,3-triazolimine; R = Me and Ph) ligands since the ligand system can easily modify its structure with the choice of a substituent R of a precursor, 1-R-1H-1,2,3-triazole-4-carbaldehyde, and another amino precursor by simple click reaction [40][41][42], Schiff-base reaction [43] and replacement of R using the method reported by L'abbé and coworkers [44,45].…”
Section: Introductionmentioning
confidence: 99%